Injectable and In Situ Phospholipid-Based Phase Separation Gel for Sustained Delivery of Altrenogest - Dongbo Li; Awn Abbas; Nanxin Li; Chao Li; Xiaoyang Ai; Lian Chen; Dongmei Dai; Gang Shu; Juchun Lin; Wei Zhang; Guangneng Peng; Haohuan Li; et al. (Gels)
Altrenogest is a key regulatory hormone for intensive and batch management of reserve sows in breeding farms. As a synthetic hormone, altrenogest could make ovaries stay at the initial stage of follicles and inhibit estrus and ovulation in animals. However, the currently used oral altrenogest solution needs to be administered continuously every day for more than two weeks in clinical practice. In this study we developed a phospholipid-based injectable gel carrying altrenogest to decrease the number of administrations, sustain release of the drug, and enhance therapeutic efficacy for clinical use. The altrenogest gel had a viscosity of 100 cP before phase transition and over 1,000,000 cP after phase transition. In vitro, altrenogest can be continuously released from gel for over two weeks. The pharmacokinetic results showed that the AUC (0–∞) of the altrenogest gel was almost double that of the altrenogest solution. The MRT (0–∞) was 40.92 ± 7.21 h and the t1/2 of the altrenogest gel was 80.03 ± 20.79 h. The altrenogest gel demonstrated excellent fluidity, ease of injectability, high drug-loading capacity, and appropriate sustained-release characteristics both in vitro and in vivo, making it a potential drug delivery system for swine production.